Remembering The Forgotten War - The Korean War In American History, 60-Minute Video And Study Guide - Kaplan, Jeffery (Teaching History: A Journal of Methods, 2001)
Remembering the Forgotten War: The Korean War in American History is an instructional video designed to supplement the study of the Korean War. Using historical photos and casual conversation, this is an easy-to-follow introduction to the events surrounding America's and the United Nations' involvement in one of our nation's most forgotten wars.